Influence of short-term operating temperatures on compression and flexural behaviour of Macro Synthetic and Steel Fibre Reinforced Concretes. (15th May 2023) - Caballero-Jorna, Marta; Roig-Flores, Marta; Serna, Pedro
Abstract: This study investigates the influence of operating temperatures on the mechanical properties of Fibre Reinforced Concretes (FRCs) when exposed during short-term periods (3 days). The studied parameters include types of fibres (macro synthetic and steel fibres), exposure to different environmental scenarios (with temperatures of −15, 5, 20, 40 and 60 °C as well as air exposition or submerged condition), and cracking conditions (precracked up to 0.5 mm or uncracked). A total of 126 cubes of 150 mm side and 182 prisms of 150 × 150 × 600 mm³ were tested in compression and flexion at the operating temperatures. The compression results obtained show similar effects in FRC and in plain concrete, with higher strength at low temperatures and slightly lower strength at higher temperatures. Similar effects were detected for the strength at the peak load, and to a minor extent, for the residual flexural strengths, for all the FRCs. Highlights: Operating temperatures effect on the mechanical behavior of FRCs was investigated. Temperatures from −15 to 60 °C were selected to simulate working scenarios. Compression and 3PBT were conducted under the pre-defined conditions. The effects on cracked element were evaluated and compared to uncracked element.